Answer:
(the relation you wrote is not correct, there may be something missing, so I will simplify the initial expression)
Here we have the equation:
We can rewrite this as:
Now we can add and subtract cos^2(x)*sin^2(x) to get:
We can complete squares to get:
and we know that:
cos^2(x) + sin^2(x) = 1
then:
This is the closest expression to what you wrote.
We also know that:
sin(x)*cos(x) = (1/2)*sin(2*x)
If we replace that, we get:
Then the simplification is:
<h2>
The required poynomial equation is .</h2>
Step-by-step explanation:
Given,
The zeros of the polynomial are - 4, - 2, 1 and 4
To find, the polynomial equation = ?
We know that,
The polynomial equation = (x - A)(x - B)(x - C)(x - D)
= (x + 4)(x + 2)(x - 1)(x - 4)
= [(x + 4)(x - 4)] [(x + 2)(x - 1)]
= ()()
= ()()
=
=
Thus, the required poynomial equation is .
Answer:
Solved for n, <em>n = 2p</em>
Step-by-step explanation:
14n + 6p - 8n = 18p
6n + 6p = 18p
6n = 12p
n = 2p
2x + 4 = 4x
4 = 2x
x = 2
Hope that helps :)